One Italian summer [large type] - Serle, Rebecca (Thorndike Press, a part of Gale, a Cengage Company, 2022)
"When Katy's mother dies, she is left reeling. To make matters worse, their planned mother-daughter trip of a lifetime looms. Now she is faced with embarking on the adventure alone. As soon as she steps foot on the Amalfi Coast, Katy begins to feel her mother's spirit. And then Carol appears--in the flesh, healthy, and thirty years old. Katy doesn't understand what is happening--all she can focus on is that she has somehow gotten her mother back. Over the course of one Italian summer, Katy gets to know Carol as a young woman. She is not who Katy imagined she might be, however, and Katy must reconcile the mother who knew everything with the young woman who does not yet have a clue"--